1992
DOI: 10.1016/s0010-9452(13)80147-5
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in Childhood Autism Shows a Dissociation of Skill and Preference

Abstract: Hand preference and hand skill were assessed in 20 children with autism, 20 normal controls and 12 children with mental retardation. 90% of the normal controls and 92% of the children with mental retardation showed concordance for hand preference and hand skill (i.e. the preferred hand was also the more skillful), whereas only 50% of the children with autism showed concordance of preference and skill, the remaining 50% preferring to use the hand which was less skillful. Children with autism also showed a lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 3 publications
6
48
1
Order By: Relevance
“…Consistency of hand preference was calculated across all pairs of replications of each item (lst with 2nd, 2nd with 3rd, 1st with 3rd), two tasks were considered consistent only if the right hand was preferred on both occasions or the left hand was preferred on both occasions. Since in the present paper only 10 items were scored, whereas in McManus et al (1992), 13 items were scored, there are minor differences in the results shown in Table I from those reported previously. It should be noted here that since, particularly among the younger subjects, a moderate number of bilateral or mixed preferences were given, the result is that laterality scores can take any value in the range 0-100%; this is in distinction to the slightly different definition used by McManus et al (1992), where of necessity scores are constrained to the range 33-100%.…”
Section: Taskscontrasting
confidence: 66%
See 4 more Smart Citations
“…Consistency of hand preference was calculated across all pairs of replications of each item (lst with 2nd, 2nd with 3rd, 1st with 3rd), two tasks were considered consistent only if the right hand was preferred on both occasions or the left hand was preferred on both occasions. Since in the present paper only 10 items were scored, whereas in McManus et al (1992), 13 items were scored, there are minor differences in the results shown in Table I from those reported previously. It should be noted here that since, particularly among the younger subjects, a moderate number of bilateral or mixed preferences were given, the result is that laterality scores can take any value in the range 0-100%; this is in distinction to the slightly different definition used by McManus et al (1992), where of necessity scores are constrained to the range 33-100%.…”
Section: Taskscontrasting
confidence: 66%
“…A review by Satz, Green, and Lyon (1989) estimated that AH accounts for approximately 40% of the handedness observed in individuals with autism and individuals with learning difficulties but is relatively rare in normal populations above the age of 4 years. However, in a study by McManus et al (1992), AH was significantly increased in children with autism compared to a mentally retarded control group and normal control group, even when degree of handedness, age, and mental age were taken into account. It should also be noted that differences in hand preference (be they direction, degree, or consistency) and assessed typically by reaching, should not be confused with differences in hand skill, assessed typically by a task such as the Annett Pegboard, and in which one can also assess the direction of the more skillful hand, and the degree of difference ~between the hands.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations